Missense mutation G296S in GATA4 is not responsible for cardiac septal defects - Ramegowda, Smitha (Medknow Publications, 2007)
BACKGROUND: The most common type of congenital heart disease is the cardiac septal defects, which has reported to be caused by a missense mutation (G296S) in exon 3 of the GATA4 gene. AIMS: The present study was undertaken to find out whether GATA4 gene is the prime cause of the septal defects in Mysore population. MATERIALS AND METHODS: GATA4 gene analyses were undertaken on 21 confirmed CHD cases by PCR and DNA sequencing. RESULTS AND CONCLUSION: Analysis of this particular mutation in 21 septal defect patients revealed that none of the patients had the mutation, indicating that this mutation is population specific or septal defect in Mysore population is caused due to mutations in other regions of the GATA4 gene.